Ion-specific effects in polyelectrolyte solutions: chain–chain interactions, chain rigidity and dynamics - Hotton, Claire; Sakhawoth, Yasine; Rollet, Anne-Laure; Sirieix-Plénet, Juliette; Tea, Lingsam; Combet, Sophie; Sharp, Melissa; Hoffmann, Ingo; Nallet, Frédéric; Malikova, Natalie (Comptes Rendus. Chimie)
In this article, ion-specific effects in aqueous solutions of polyelectrolytes (PEs) are addressed. We focus on ionene cationic chains, featuring simple structure, absence of side groups, and very regular chain charge density. Ion-specific effects in ionene solutions are demonstrated using a series of monovalent (halide) counterions. The study combines both static and dynamic measurements by small angle neutron scattering, neutron spin echo (NSE), and pulsed field gradient NMR (PFG-NMR). Ion-specific effects are a phenomenon at high PE concentration, and the nature of the counterion is seen to influence drastically ionene chain–chain interactions via what we refer to as “ion-specific screening”. The origin lies in the closer approach of large, highly polarisable counterions to the chain backbone, leading to more constricted counterion clouds. Equally affected is the local chain rigidity as well as collective and self-diffusion coefficients at larger scales. Small, nonpolarisable, strongly hydrating counterions, here F- ions, lead to locally rigid chains. For such chains, the nm-scale collective dynamics as seen by NSE is the fastest while self-diffusion seen at the µm scale by PFG-NMR is the slowest. In other words, the loss of charge on the chain due to ion-specific screening has the opposite effect on collective diffusion and self-diffusion of the chains.